Stravinsky His Thoughts and Music - Jarzębska, Alicja (Eastern European Studies in Musicology, 2020)
This book is an attempt at a new interpretation of Stravinsky's thoughts about music and art, an interpretation made in dialogue with the philosophy of new music and 19th-century artistic ideas. It is also a proposal for a new method of analysing the construction of his musical masterpieces (for example a proposal of new formal sound-units: partons with perceptual invariance), a method in-spired by research into cognitive psychology. Furthermore, in the analysis of Stravinsky's music, the author emphasises its connection with the Eastern and Western traditions of European culture and links with Plato's triad of values.